METHODS OF TREATMENT FOR STRESS URINARY INCONTINENCE (SUI): A REVIEW OF CURRENT RESEARCH - Antoni Kujawski; Anna Opalińska; Cezary Lubas; Paula Folta; Joanna Kłosowska; Karolina Błądzińska; Maciej Błądziński; Dominika Machała; Piotr Świerczek; Kacper Szeląg (International Journal of Innovative Technologies in Social Science, 2026)
Research objectives: This study aims to provide a comprehensive analysis of treatments for Stress Urinary Incontinence (SUI). Through a detailed discussion and review of the evidence, we examine conservative, pharmacological, and surgical approaches, highlighting their therapeutic benefits. This review also synthesizes the current literature to summarize the advantages and limitations of each method in relation to specific patient groups.Methods: A literature search was conducted in PubMed and Google Scholar, with emphasis on publications from 2015-2025. The search strategy included terms such as ‘stress urinary incontinence’, ‘pessary’, ‘surgical intervention’, and ‘treatment choice’.Key findings and conclusions: Stress urinary incontinence (SUI) is a common condition affecting women across a wide range of ages. Effective management requires an individualized approach in which the therapeutic method is selected based on the severity of symptoms, the patient’s anatomical characteristics, coexisting chronic diseases, reproductive plans, and personal expectations regarding treatment outcomes.First-line therapy for SUI consists of conservative methods, including pelvic floor muscle training, behavioral modification, weight reduction, pessary use, and topical estrogen therapy in postmenopausal women. Although the benefits of duloxetine have been demonstrated, its clinical utility is limited by adverse effects and contraindications during pregnancy, resulting in a restricted role for pharmacotherapy in SUI management. When conservative treatment fails to provide adequate improvement, surgical intervention should be considered. Current evidence supports the mid-urethral sling (MUS) as the preferred surgical method due to its long-term effectiveness and favorable safety profile. MUS has largely replaced earlier techniques such as Burch colposuspension, although the latter may still offer advantages in selected patient groups.In summary, the treatment of SUI encompasses a wide range of therapeutic options, each with distinct benefits and limitations. Therefore, shared decision-making that incorporates the patient’s medical characteristics and individual preferences is crucial for achieving optimal treatment outcomes.